2020
DOI: 10.1097/ico.0000000000002487
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Safety and Efficacy of a Low-Temperature Plasma Surgical System for Pterygium

Abstract: Purpose: Surgical excision is the standard treatment for pterygium. This study was conducted to evaluate the safety and efficacy of a novel technique using low-temperature plasma (LTP) for excision and hemostasis in pterygium surgery. Methods: A prospective, comparative, and randomized clinical trial was conducted on 60 patients (60 eyes) undergoing pterygium excision with conjunctival autografts using fibrin glue. Patients were equally divided into the following 2 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Huang et al reported that low-temperature plasma is safe and e cient for pterygium surgery, but the optimal energy choice for pterygium surgery and its correlation with in ammatory factors have not yet been elucidated. 34 In our research, we have veri ed the safety of low-temperature plasma radiofrequency ablation for corneal tissue through animal experiments. In animal experiments, we chose the ablation energy of 20, 15, 10J/cm 2 for the safety analysis of lowtemperature plasma radiofrequency ablation.…”
Section: Observation Of Clinical Indicatorsmentioning
confidence: 89%
“…Huang et al reported that low-temperature plasma is safe and e cient for pterygium surgery, but the optimal energy choice for pterygium surgery and its correlation with in ammatory factors have not yet been elucidated. 34 In our research, we have veri ed the safety of low-temperature plasma radiofrequency ablation for corneal tissue through animal experiments. In animal experiments, we chose the ablation energy of 20, 15, 10J/cm 2 for the safety analysis of lowtemperature plasma radiofrequency ablation.…”
Section: Observation Of Clinical Indicatorsmentioning
confidence: 89%
“…Huang H. et al, concluded that low-temperature plasma ablation is effective and safe for treating pterygiums. It reduces the amount of time needed for surgery, reduces inflammation and improves the graft stability without raising the risk of complications [ 36 ]. The results of Wahaj Saleem ‘s experiment show that the treatment enhances the rate of scratch wound closure in a human corneal epithelial (HCE) cell line and considerably reduces the incidence of mucopurulent corneal ulcers and the severity of edema (swelling) in P. aeruginosa -infected rabbit corneas [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the most commonly researched applications within the field of plasma medicine are dentistry [13], dermatology [14,15], oncology [16], infection control, and sterilization [17][18][19]. However, there is further potential for applications of cold plasma treatments in a variety of other areas, including ophthalmological and neurological applications [20][21][22]. Some applications of plasma medicine extend beyond the realm of tissue or clinical treatments.…”
Section: History and Current State Of Plasma Medicinementioning
confidence: 99%